Short-Term Quality-of-Life Changes after Endoscopic Pituitary Surgery Rated with SNOT-22 - Zimmer, Lee A.; Shah, Ojas; Theodosopoulos, Phillip V. (Journal of Neurological Surgery Part B: Skull Base, 2014)
Objective Little data exist on short-term quality-of-life (QOL) outcomes, specifically sinonasal measures, after endoscopic pituitary surgery.Design Prospective case series assessed sinonasal QOL before and after the transnasal endoscopic approach to the sella with resection of nasal cavity and sinus tissues.Setting/Participants/Main Outcome Measures A total of 39 adults scheduled to undergo resection for a pituitary mass preoperatively completed the Sinonasal Outcome Test-22 (SNOT-22). Rating various QOL issues, testing repeated postoperatively at 1 month by 37 patients and 3 months by 35 patients, was analyzed (paired Student t test).Results SNOT-22 scores (5-point scale; total: 110) averaged 23.4 preoperatively and 27.6 at 1 month but had significantly improved to 16.2 at 3 months (p = 0.03). Emotional well-being parameters (e.g., sadness, frustration, concentration, productivity, fatigue) significantly improved 3 months postoperatively (p < 0.05). Physiologic parameters (e.g., olfaction, obstruction, postnasal drainage) that had worsened at 1 month (< 0.05) then normalized at 3 months.Conclusion Total ratings for sinonasal QOL shows that SNOT scores were comparable between preoperative and 1-month testing but were improved significantly at 3 months. Individual questions showed marked improvement in emotional well-being and temporary physiologic changes after surgery. Our findings give surgeons information about what patients can expect immediately after transnasal endoscopic pituitary surgery.
Keywords: quality of life; sphenoid sinus; pituitary surgery; endoscopy